Parentalia, Lemuria, Larentalia, Compitalia, Mundus Patet – ceremonie ku czci zmarłych w rzymskim systemie wierzeń - Kaczor, Idaliana (Collectanea Philologica, 2019)
The ceremonies in honour of the dead – Parentalia, Lemuria, Larentalia, Compitalia, mundus patet – corresponded with the spiritual needs of the Romans. The purpose of the religious event recorded in the fasti usually resulted from its placing at a specific moment of the religious year, which was of great significance to the sacral community. A religious intuition in the Romans gave ground to the combination of official ceremonies in the honour of ancestors with important agricultural dates i.e. defined periods for the evaluation of time and space, which, often, accepted the form of apotropaic festivities with magical rituals. Often, the ceremonies of the turn of the year guaranteed human and animal fecundity as well as vegetative fertility.